Clinical application of breathing-adapted 4D CT: image quality comparison to conventional 4D CT - Werner, René; Szkitsak, Juliane; Madesta, Frederic; Büttgen, Laura; Wimmert, Lukas; Sentker, Thilo; Fietkau, Rainer; Haderlein, Marlen; Bert, Christoph; Gauer, Tobias; Hofmann, Christian (Strahlentherapie und Onkologie, 2023)
Purpose: 4D CT imaging is an integral part of 4D radiotherapy workflows. However, 4D CT data often contain motion artifacts that mitigate treatment planning. Recently, breathing-adapted 4D CT (i4DCT) was introduced into clinical practice, promising artifact reduction in in-silico and phantom studies. Here, we present an image quality comparison study, pooling clinical patient data from two centers: a new i4DCT and a conventional spiral 4D CT patient cohort. Methods: The i4DCT cohort comprises 129 and the conventional spiral 4D CT cohort 417 4D CT data sets of lung and liver tumor patients. All data were acquired for treatment planning. The study consists of three parts: illustration of image quality in selected patients of the two cohorts with similar breathing patterns; an image quality expert rater study; and automated analysis of the artifact frequency. Results: Image data of the patients with similar breathing patterns underline artifact reduction by i4DCT compared to conventional spiral 4D CT. Based on a subgroup of 50 patients with irregular breathing patterns, the rater study reveals a fraction of almost artifact-free scans of 89% for i4DCT and only 25% for conventional 4D CT; the quantitative analysis indicated a reduction of artifact frequency by 31% for i4DCT. Conclusion: The results demonstrate 4D CT image quality improvement for patients with irregular breathing patterns by breathing-adapted 4D CT in this first corresponding clinical data image quality comparison study.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 4D CT; 4D radiotherapy; Image artifacts; Image quality